Strategi Guru Dalam Menumbuhkan Kemampuan Berpikir Logis Anak Di Taman Kanak-Kanak Kabupaten Bone - Andi Iting (Sipakatau: Jurnal Pendidikan dan Kebudayaan, 2025)
This study discusses the strategies of teachers in developing children's logical thinking skills in Bone Regency. The purpose of this study is to determine the logical thinking skills of children in Kindergartens in Bone Regency. Describe the strategies used by teachers in developing children's logical thinking skills in Kindergartens in Bone Regency. Data collection techniques used in this study are observation, interviews, and documentation. Based on the results of research conducted in Kindergartens in Bone Regency, it was concluded that children's logical thinking skills in Kindergartens in Bone Regency have not developed optimally. This can be seen when children do not yet recognize the differences based on the size of more than, less than, and most / ter, and children do not fully recognize the concept of many and few, children do not yet recognize the cause and effect of the environment, for example the wind blowing. The strategy used by teachers to develop children's logical thinking skills in kindergartens in Bone Regency involves play strategies, including encouraging children to recognize the names of objects around them, basic colors (such as red, green, yellow), shapes, sizes, textures, sounds, properties, functions, and characteristics of objects in the surrounding environment (such as stones, leaves, twigs, cutlery, and so on) to be used in mathematical games such as counting, measuring, grouping objects by color and shape, sorting objects, comparing objects (large-small, tall-low, long-short), and arranging patterns.